Pengaruh Program Pemutihan Pajak Kendaraan Bermotor, Pembebasan Bea Balik Nama (BBN) Kendaraan Bermotor, dan Kualitas Pelayanan Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor dengan Sosialisasi Perpajakan sebagai Variabel Moderating - Baihaqi Ammy (Politeknik Ganesha Medan, 2023)
The purpose of this study was to determine the effect of the Motor Vehicle Tax Bleaching Program, the Exemption of Transfer of Name Duties and the Quality of Tax Services on the Compliance of Motor Vehicle Taxpayers with Tax Socialization as a Moderating Variable at UPT. Samsat Medan Utara. The research approach used in this study is associative. The sampling technique used is incidental sampling. Data was collected by distributing questionnaires to motorized vehicle taxpayers registered with the UPT. North Medan Samsat. The data analysis technique used in this study is the classical assumption test, multiple linear regression, t-test, f test, coefficient of determination, and moderating regression analysis using the IBM SPSS Version 26.0 program. The results of this study indicate that partially Bleaching Motor Vehicle Taxes has an effect on compliance with motorized vehicle taxpayers, Exemption of Transfer of Names for Motorized Vehicles has an effect on compliance with motorized vehicle taxpayers and the Quality of Tax Services does not affect compliance with motorized vehicle taxpayers. Simultaneously the Motor Vehicle Tax Bleaching Program, the Exemption of Transfer of Ownership of Motor Vehicles, and the Quality of Tax Services have a significant effect on the compliance of motorized vehicle taxpayers. Motor Vehicle Taxpayer Compliance. Socialization of Taxation as a moderating variable is not able to moderate the relationship between Tax Service Quality and Motor Vehicle Taxpayer Compliance UPT. Samsat Medan Utara.